Protection of hepatotoxicity using Spondias pinnata by prevention of ethanol-induced oxidative stress, DNA-damage and altered biochemical markers in Wistar rats - Shoaib Shadab Iqbal; Md. Mujahid; Sayed Mohammad Kashif; Mohammad Khalid; Badruddeen; Muhammad Arif; Paramdeep Bagga; Juber Akhtar; Md. Azizur Rahman (Integrative Medicine Research, 2016)
Background: Traditional systems of medicine use herbal drugs for hepatoprotection. Thus, the study was designed to evaluate the hepatoprotective and antioxidant effects of Spondias pinnata bark extracts against ethanol-induced liver injury in Wistar rats. Methods: Group I animals were treated with 1 mL/kg 0.3% carboxymethyl cellulose and Group II with 12 mL/kg 50% ethanol for 8 consecutive days. Groups III–VII animals were first treated with 400 mg/kg petroleum ether extract, chloroform extract, acetone extract (AE), ethanol extract (EE), and 100 mg/kg silymarin, and then 12 mL/kg 50% ethanol orally after 2 hours pretreatment each day for 8 consecutive days. Six hours after the last dose, blood was withdrawn. The hepatoprotective activity was assessed by several biochemical and antioxidant parameters. It was accomplished by the histopathology and DNA fragmentation study of liver tissues. Results: Treatment with S. pinnata extracts, mainly AE and EE significantly (p < 0.05–0.01) and dose-dependently prevented the ethanol-induced increase in serum levels of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, lactate dehydrogenase, cholesterol, bilirubin, and malondialdehyde, and decrease in reduced glutathione, catalase, superoxide dismutase, and albumin. They also attenuated the ethanol-induced DNA damage. Hepatoprotective potential of the extract was less than that of standard drug silymarin. Results of the study were well supported by the histopathological observations. Conclusion: S. pinnata extracts AE and EE possess a potent hepatoprotective effect against ethanol-induced liver injury in Wistar rats, and protect them from hepatotoxicity by prevention of ethanol-induced oxidative stress, DNA-damage and altered biochemical markers.